GE_GERICHTE P/14263/2016 vom 3. September 2019 - GE Cour de justice (2019)
CLASSEMENT DE LA PROCÉDURE;ACTION EN INTERDICTION;LIEU DE TRAVAIL;VIOLATION DE DOMICILE;ERREUR DE DROIT(DROIT PÉNAL) | CPP.319; CP.186; CP.21; CP.52